Mechanisms and Implications of CDK4/6 Inhibitors for the Treatment of NSCLC - Zhang, Jinmeng; Xu, Dayu; Zhou, Yue; Zhu, Zhengfei; Yang, Xi (Frontiers in Oncology, 2021)
Cyclin-dependent kinases (CDKs) are critical regulators of cell cycle progression in malignant cells, functioning through complex molecular interactions. Deregulation of CDK dependent pathways is commonly found in non-small cell lung cancer, and these derangements suggest vulnerabilities that can be exploited for clinical benefit. CDK4/6 inhibitors can prevent tumor cells from entering the G approved 1 and S phases, which can be used in hormone receptor positive breast cancer, and combined with endocrine therapy, has become the first-line standard treatment for patients with breast cancer. CDK4/6 inhibitors have been studied in a series of explorations and demonstrated to have brought great clinical benefits to patients and gave more encouragement to physicians and researchers, thereby showing potential as a new therapeutic agent. A series of preclinical and clinical studies have been carried out on CDK4/6 inhibitors in NSCLC, and have been achieved some results, which may become a new treatment in the future. This review focuses on research progress on CDK4/6 inhibitors in NSCLC, particularly the mechanisms of action, drugs, clinical research progress, and future application.